Woman of Board Directors, Leverage, Sales Growth, Institutional Ownership, and Earnings Management - Rahel Litaya; Rousilita Suhendah (Graduate Program of Universitas Tarumanagara, 2023)
This study aims to determine the effect of the size of the female board of directors and commissioners, leverage, and sales growth with the moderating variable of institutional ownership on leverage on earnings management in the real estate and construction which listed on the Indonesia Stock Exchange for the 2017-2020 period. Data processing was carried out with Eviews. The sample was selected with purposive sampling method. The results showed that the size of the female board of directors and sales growth significantly negatively affected earnings management. The female board of directors can reduce earnings management because women in leadership positions in businesses are capable of making wise and moral decisions. The higher the sales growth, the lower the earnings management. Companies have a high sales growth rate means that the company's profit is also high. Managers are not motivated to increase profits because their interests of managers are the same as stakeholders' interests. Managers have the same information as stakeholders, so there is no information asymmetry. Leverage has no significant effect on earnings management. Leverage in earnings management has a significant negative impact on moderating institutional ownership.